Students’ Perceptions towards Online Education during COVID-19 Pandemic: An Empirical Study - Sami Hussein Hakeem Barzani; Rayan Jalal Jamil (International Journal of Social Sciences & Educational Studies, 2022)
The outbreak of COVID-19 has had a critical impact on the educational system around the world. Unwillingly, all educational institutions transited to online teaching. This study endeavoured to address the perceptions of Kurdish EFL university students of online education compared to on-campus education in terms of domains of preference, effectiveness, learning satisfaction, and challenges. To do so, data were collected quantitively as well as qualitatively. A sample of 200 university Kurdish EFL university students (112 female & 88 male) from private and public universities of the Iraqi Kurdistan Region-Erbil participated. The results showed that the overwhelming majority of the students have a negative attitude toward online education. Similarly, they preferred and considered on-campus education more effective. The findings also revealed that the overwhelming majority of the students stated online education do not suffice their learning satisfaction. Finally, the challenges articulated by the students during online education included external factors, such as unstable internet connection, electricity besides internal ones, like time management, concentration difficulties, and opening cameras due to social issues.